Project report and feasibility study of an appropriate technology for manufacture of whiteware pottery on cottage basis in rural areas - Garg, M. K. (Mahaish Krishna), 1918- (Project report and feasibility study series ;, 1979)
Cover title: Cottage whiteware pottery: project proposal and feasibility report.